Enhancing Rwanda's Global Competitiveness: Evaluating the Impact of 'Made in Rwanda' Policies on Local Manufacturing Growth and Innovation - SIKUBWABO, Theoneste (International Journal of Scientific Research and Management (IJSRM), 2024)
The study aimed at Enhancing Rwanda's Global Competitiveness: Evaluating the Impact of 'Made in Rwanda' Policies on Local Manufacturing Growth and Innovation. The specific objectives of the study were: to establish the impact of ‘Made in Rwanda’ policies on the growth of local manufacturers in Kenya sectors between 2017 and 2023; and to examine the extent to which ‘Made in Rwanda’ policies have improved the competitive advantage of local manufacturers in regional and international markets. Descriptive research, a method of gathering data, was used in this study to address inquiries about the present state of the research participants. The sample size of 246 respondents was proportionally distributed across the different sectors. The main instrument that was used for data collected was a semi-structured questionnaire. Descriptive statistics was used to show trends and inferential statistics was used to anlyse the relation between the various variables with multiple regression analysis crowing the hypothesis testing. Crucially insightful results came from the regression study done to investigate the link between the 'Made in Rwanda' policies and local manufacturers' competitive advantage. Here, the regression equation could be shown as Y=2.5+0.7X1+0.5X2+ε. With an intercept (β0) at 2.5, local manufacturers' competitive advantage is expected to be 2.5 units should both independent variables equal zero. With β1=0.7, the coefficient for Growth 'Made in Rwanda' Policies shows a direct link whereby competitive advantage rises by 0.7 units for every unit increase in growth policies. With p < 0.001, this is statistically significant and indicates rather strong evidence on the favorable impact of growth policy on company competitive advantage. With β2=0.5, the coefficient Competitive Advantage "Made in Rwanda" Policies also shows that, alongside every unit increase in competitive advantage policies, each caused a 0.5 unit increase in competitive advantage of manufacturers. This is statistically significant (p = 0.01) and once more shows to be especially crucial for raising competitiveness. For local producers, the correlated independent variables explain 68 percent of the variance in competitive advantage. All things considered, 'Made in Rwanda' policies have greatly helped the local manufacturer to grow over the past few years. According to the study's findings, strategic actions including policy incentivizing, infrastructure access, and capacity-building initiatives have improved production capability and market positioning. Thanks to these policies, local producers will not only develop but also be more suited to compete against foreign players on their path into regional and worldwide markets. This rightly emphasizes the need of a constant and adequate government support as well as an ongoing assessment of these policies to guarantee they remain relevant and efficient in handling the problems encountered in the manufacturing sectorKeywords: 'Made in Rwanda' policies, local manufacturers, competitive advantage, production output, employment growth, export volume, product differentiation, policy incentives, infrastructure, government support programs, trade agreements, and capacity building.